Impact of pacifier use and parenting characteristics on toddlers’ vocabulary development - Barca, Laura; Mazzuca, Claudia; Borghi, Anna M. (Frontiers in Psychology, 2025)
IntroductionThis study investigated the relationship between pacifier use and early vocabulary development, specifically hypothesizing that pacifier use would correlate with a reduced overall vocabulary size and a specific underrepresentation of abstract words.MethodsWe recruited a sample of 98 typically developing children aged 18-36 months. Data collection included information on pacifier use, feeding habits, parenting styles, parental satisfaction, and vocabulary. Vocabulary was assessed using the MacArthur-Bates Communicative Development Inventory.ResultsContrary to our initial hypotheses, we found no significant association between pacifier use and either overall vocabulary size or the acquisition of abstract words within this age range. However, we observed a correlation between pacifier use and feeding type, as well as an unexpected positive association with a higher paternal sense of efficacy. Pacifier use did not show a link to specific parenting styles.DiscussionOur findings suggest that pacifier use in children aged 18-36 months does not negatively impact early vocabulary development. While these results offer valuable insights, further research is warranted to explore the complex factors influencing language development and the potential long-term impact of pacifier use beyond 36 months of age.